2009
DOI: 10.1002/jnr.22045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a promoter polymorphism on the transcription of nitric oxide synthase 1 and its relevance to Parkinson's disease

Abstract: Transcriptional changes of the enzyme nitric oxide synthase I (NOS1) are believed to play a role in the development of many diseases. The gene for NOS1 has 12 alternative first exons (1A-1L). The 1F exon is one of the most highly utilized first exons in the brain and has a polymorphism ((TG)(m)TA(TG)(n)) located in its promoter region. The polymorphism's length has been suggested to affect NOS1 transcription and play a role in Parkinson's disease (PD); however, the actual influence of the polymorphism on NOS1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…The expression of NOS1 in different tissues seems to be mediated by the untranslated leader exon; exons 1c and 1f are the predominant first exons expressed in the human brain (Bros et al 2006;Reif et al 2006). A repeat polymorphism in the promoter region of NOS1 exon 1f (Ex1f-VNTR) which affects gene expression and neuronal transcriptome (Reif et al 2009;Rife et al 2009) is linked to severity of schizophrenia (Reif et al 2006) and Alzheimer's disease (Galimberti et al 2007). Recently, it was found that NOS1 Ex1f-VNTR as well influences aggression, hyperactivity, cluster B personality disorders and impulsivityrelated personality phenotypes in humans (Reif et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of NOS1 in different tissues seems to be mediated by the untranslated leader exon; exons 1c and 1f are the predominant first exons expressed in the human brain (Bros et al 2006;Reif et al 2006). A repeat polymorphism in the promoter region of NOS1 exon 1f (Ex1f-VNTR) which affects gene expression and neuronal transcriptome (Reif et al 2009;Rife et al 2009) is linked to severity of schizophrenia (Reif et al 2006) and Alzheimer's disease (Galimberti et al 2007). Recently, it was found that NOS1 Ex1f-VNTR as well influences aggression, hyperactivity, cluster B personality disorders and impulsivityrelated personality phenotypes in humans (Reif et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although nNOS interacts with environmental risk factors associated with PD [10,11], conflicting results deny this notion. A few SNPs in nNOS are found to be associated with PD risk in a population while the same SNPs are not found to be associated in other population [10,[12][13][14][15]. Although lack of association in a few studies [13,16] is reported, it is widely accepted that nNOS polymorphism acts as modifiable factor of PD risk.…”
Section: Introductionmentioning
confidence: 91%
“…Owing to variation in environment and lifestyle factors as well as ethnicity of north Indians as compared with the rest of the world, it was worthwhile to investigate the association of NOS1 SNPs with PD risk. Since two SNPs located in exon 18 and exon 29 of nNOS gene exhibit variable association with PD risk in different populations [10,[12][13][14][15][16][17], the current study aimed to investigate their association with PD risk and also with nitrosative and oxidative stress indicators.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the transcription level of NOS1 are believed to play a role in the development of many diseases [52] . NOS inhibitors may be useful to treat L-Dopa-induced dyskinesia [53] .…”
Section: Neuronal Nitric Oxide Synthase (Nnos) and Inos Inhibitorsmentioning
confidence: 99%